Character Education Program Management in Islamic Primary Schools: A Sequential Explanatory CIPP Evaluation - Siti Kamilah; Rita Sriayu; Suherman Suherman; Zurqoni Zurqoni; Heri Retnawati (Universitas Nurul Jadid, 2025)
Character education in Indonesian madrasah continues to face a structural challenge: programs are designed with ambition but evaluated without rigor. This study assessed the ecotheological and religious nationalist character reinforcement program implemented through a love-based curriculum in PAI learning at MI Syaichona Cholil Balikpapan, using Stufflebeam's CIPP model as the evaluative framework. A sequential explanatory mixed-methods design was employed, combining a five-point Likert scale questionnaire administered to 84 students and 120 parents, observation of 36 PAI learning sessions, in-depth interviews with one madrasah principal and four PAI teachers, and documentary analysis. The context evaluation confirmed strong policy alignment and genuine field demand, with 91.7% of teachers affirming the program's necessity. Input evaluation revealed a critical competency gap: only 45.8% of teachers demonstrated adequate understanding of the love-based curriculum. Process evaluation identified a 27-percentage-point discrepancy between lesson plan intentions and standardized assessment practice. Despite these constraints, the product evaluation yielded statistically significant character gains in both ecotheological character (d = 0.69) and religious nationalist character (d = 0.70), both at p < .001. Teacher relational competence emerged as the primary mediating variable determining program effectiveness. These findings establish that the love-based curriculum possesses sufficient pedagogical potency to generate meaningful character development even under partially optimized conditions, provided that teacher formation is treated as a central institutional priority rather than a supplementary concern.